The Hooded Man of the National Stadium: Exploring Collaboration in the Dictatorship Through the Case of Juan Muñoz Alarcón - Guerra, Felipe (Revista de Historia Social y de las Mentalidades, 2025)
This paper examines the collaboration of former left-wing militants with the Chilean military dictatorship, focusing on the case of Juan Muñoz Alarcón, a former socialist who became involved in repression, covering his face to identify and denounce individuals inside the National Stadium, which had been turned into a detention center during that period. After years of participation in state security agencies, Muñoz Alarcón attempted to distance himself, providing a detailed testimony to the Vicaría de la Solidaridad before his murder. The study seeks to unravel the dynamics of collaboration, characterize its effects, and analyze Muñoz Alarcón’s trajectory. The concept of the “grey zone,” proposed by Primo Levi, is used as an explanatory tool to understand the construction of the collaborator.